LANGUAGE CHOICE AND SOCIAL STATUS IN UZBEK ONLINE COMMUNITIES - Polvonniyozova Makhliyo Uktamjonovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article deals with the issues based on analyzing the relationship between language choice and social status within Uzbek online communities. In multilingual digital environments, individuals often switch between Uzbek, Russian, and English to construct identity and signal social positioning. Drawing on sociolinguistic theories and digital discourse analysis, the research highlights how English is frequently associated with modernity and global identity, and Uzbek with national and cultural affiliation. The findings demonstrate that language choice is not neutral but reflects deeper socio-cultural hierarchies in online communication. The study contributes to understanding digital multilingualism in post-Soviet contexts.